Tourism-marketing performance metrics and usefulness auditing of destination websites - Woodside, Arch G. (Advances in culture, tourism and hospitality research, 2010)
This volume provides specific answers to hard questions about how to create valid metrics to measure the effectiveness of tourism advertising and the usefulness of destination marketing websites. An extensive literature review describes 40+ years of research on the effectiveness of tourism advertising and the slow advancement to using valid impact metrics field experiments with alternative ad treatment and placements. Several authors undertake information-usefulness audits on DMO (destination management office) websites and provide practical check lists. Tourism website comparisons include: Maine, Massachusetts and New York; Genoa, Marseilles and Valencia; France, Spain and Portugal; and China, Poland, Russia and Thailand, against each other as well as the Lonely Planet websites. Content analysis of consumer-generated advertisements that promote visits to third places, in this case Starbucks coffee shops and Chipotle restaurants, makes an intriguing study. The final paper gives a thick description of the dynamics of the governments role in shaping Chinas domestic, inbound, and outbound tourism industry and contributes to building a behavioral theory of government-firm relationships.